2019
DOI: 10.1097/bor.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Depression and the risk of rheumatoid arthritis

Abstract: Purpose of review Rheumatoid arthritis (RA) is associated with negative changes in mental health. This is generally attributed to symptoms of inflammation and the adverse impact of RA on quality of life and functioning. Until recently, causal pathways in the opposite direction have not been fully appreciated. This review examines the recent literature on the risk of RA associated with depression. Recent findings Current literature links depression with an increased risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 42 publications
6
81
4
3
Order By: Relevance
“…Getting more and more insights into the reciprocity between depression and RA, current literature links depression with an increased risk for RA 18. A recent retrospective population-based cohort study covering data for 26 years, from 1986 to 2012, identified that depression even increases the risk for developing RA by 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Getting more and more insights into the reciprocity between depression and RA, current literature links depression with an increased risk for RA 18. A recent retrospective population-based cohort study covering data for 26 years, from 1986 to 2012, identified that depression even increases the risk for developing RA by 38%.…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based cohort in Taiwan, patients with rheumatoid arthritis were 2.06 times more likely to develop depression compared with the control patients 47. The high prevalence and incidence of depression among patients with arthritis may be attributed to several factors, including the impact of the diagnosis with no cure, arthritis symptoms and flare-ups, loss of work productivity and side effects of medications 48. In the current study, we found that chronic digestive disorders at baseline conferred a higher risk for depressive symptoms over time.…”
Section: Discussionmentioning
confidence: 99%
“…Potential participants with serious depressive symptoms should be referred immediately to a mental health professional. Individuals with these chronic conditions are particularly vulnerable to the deleterious effects of affective symptoms, since symptoms of depression are a known risk factor for non-compliance with medical treatment and adverse health outcomes 48 49 57 58…”
Section: Discussionmentioning
confidence: 99%
“…They also perceive that support from others with similar experiences is uniquely valuable (Hughes et al, ). However, patients with IA have a higher predisposition to develop depression or psychological distress (Howells et al, ; Vallerand, Patten, & Barnabe, ). Depression increases the risk of disease flares; decrease rates of remission and interferes with patients' coping strategies, clinical management (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Depression increases the risk of disease flares; decrease rates of remission and interferes with patients' coping strategies, clinical management (e.g. medication compliance) and quality of life (Vallerand et al, ). In the opposite case, patients with less depressed mood and dissatisfaction with life have higher levels of self‐efficacy and role balance (Coty, Salt, Myers, & Abusalem, ).…”
Section: Introductionmentioning
confidence: 99%